Teorie sociologiche alla prova - GIOVANNINI, Paolo (Manuali - Scienze Sociali, 2009)
Intellectual integrity and a challenge to rhetoric are the two strategic objectives of those who take up the hazardous path of sociological knowledge. This book does not presume to respond fully, but at least attempts to target these aims. The fruit of many years' teaching and research experience, it adopts a line of interpretation that highlights the point of view of the social agent considered in his close, symbiotic and procedural relation with the society in which he acts; this society is not abstract and generic but explored and construed in the tangible dimension of daily life and social relations. The book is organised with a practically identical layout in all the chapters: in dialogue format it proceeds from the identification of the categories central to the issue addressed through to its empirical application/s, hinging the two together with contributions from the sociological school or writer most relevant to the subject in question.